A user-friendly sofware for generating patient-specific masking noise in relieving the incurable tinnitus - Fırat, Murat. (Thesis (M.S.) - Bogazici University. Institute of Biomedical Engineering, 1996., 1996)
Tinnitus is a widely suffered complaint concerning the human auditory system. The tinnitus-stricken patient is generally characterized with hearing loss and suffers from an almost never-ending sound in his ears. These whistle, wind, water fowl, water flow, hissing, etc.-like sounds are always subjective and thus, their detection is quite difficult. Masking the tinnitus sound is one of the most successful non-invasive methods of coping with the tinnitus. In order for the masking method to be acceptable and successful, the masking sound should be individually tailored for the patient. In this thesis, a special computer software has been improved which will enable the physician to detect the tinnitus frequency necessary for masking and which will especially be learnt and conducted easily by the patients. Such a system, consisting of a PC, equipped with a sound card and specially developed software has been proposed and its cost-effectiveness has been demonstrated. The system will for sure speed up the tedious work needed for the determination of the tinnitus frequencies and for the generation of the matching masking sound which is a time-consuming process for both the physician and the patient. A small clinical testing and experience proved that this time-consuming detection of pitch-frequency is much more shorter and simpler with this new software. This software, first of all, applies a simple audiometric test between 125-8000 Hz. The main stage in which the tinnitus frequency is detected, has an algorithm based on the Newton-Rhapson method. This process begins with the application of pure sinusoidal tone at 860 Hz that will change eventually according to the patient's trials to find the relieving sound for him. The scanning of tinnitus frequencies between 125 and 8000 Hz is repeated three times respectively. When this process is completed, a narrow-band white noise with a pure tone at the pitch frequency is synthesized. The software also includes a database for the personal information and the measurement data of the patients.
Keywords: Tinnitus.